A NORMATIVE LEGAL STUDY OF THE INDEPENDENCE OF THE JUDICIAL BRANCH OF THE CONSTITUTIONAL COURT WITHIN THE SYSTEM FOR APPOINTING CONSTITUTIONAL COURT JUSTICES IN INDONESIA - Tomi Agustian; Dinda Setiawati (ANAYASA : Journal of Legal Studies, 2026)
Article 24, paragraph 1 of the 1945 Constitution states, “The judicial branch is an independent branch of government responsible for administering justice to uphold the law and justice,” However, Article 24C, paragraph (3) of the 1945 Constitution of the Republic of Indonesia stipulates that the Constitutional Court shall consist of nine constitutional justices appointed by the President, with three nominees each proposed by the Supreme Court, the People’s Representative Council, and the President,” and in Law No. 7 of 2020 on the Constitutional Court, Article 18(1) states that three Constitutional Court Justices are nominated each by the Supreme Court, the People’s Representative Council, and the President. Thus, the President, the Supreme Court, and the People’s Representative Council. This study aims to examine the independence of the Constitutional Court in Indonesia. It employs a normative legal approach. The conclusion is that the nomination process for the nine Constitutional Court Justices—proposed by the President, the House of Representatives, and the Supreme Court—may influence a judge’s decision-making, particularly regarding the review of legislative acts issued by the House of Representatives and the President, as well as the review of laws —which falls under the authority of the President and the Supreme Court—as well as adjudicating election disputes and the dissolution of political parties, all of which are within the Constitutional Court’s jurisdiction as stipulated in the 1945 Constitution,  thereby undermining the intent of Article 24, paragraph 1, of the 1945 Constitution, which safeguards the independence of the judiciary in upholding justice in accordance with the ideals of the 1945 Constitution.